SISTEM INFORMASI ALUMNI PROGRAM STUDI INFORMATIKA UNIVERSITAS TEKNOLOGI SUMBAWA BERBASIS WEB - Rodianto; Muhammad Abduh Robbani; Nora Dery Sofya (Program Studi Informatika Universitas Teknologi Sumbawa, 2020)
In the world of education the utilization of information technology is something that must be implemented, one of which is the use of the internet which can be used as a medium for disseminating information. Informatic Study Program of Sumbawa University of Technology is a study program that has graduated many alumni, but so far there is no portal that can manage information regarding the whereabouts of its alumni. This causes the study program difficulties in getting the latest information of the alumni when needed. Therefore, in this research a website-based alumni information system was designed which aims to facilitate the Informatic Study Program of Sumbawa University of Technology in managing and searching for information related to alumni data. In building this system researchers used the PHP programming language with CodeIgniter Framework and MySQL as the database. Then for the development of this software is using Waterfall model. It is hoped that when this system is implemented it can be used by study programs and alumni in managing alumni information, making it easier and faster to conduct data collection and reporting of existing alumni data.